Comparison of Passive and Active Exploration Flight Test 1 Radiation Detector Measurements with Trapped Proton and Vehicle Shielding Model Calculations - Nounu, Hatem; Gaza, Ramona; Lee, Kerry; Bahadori, Amir A. (My University, 2016)
The Battery-operated Independent Radiation Detector and Radiation Area Monitors ?own on-board the Exploration Flight Test 1 mission provide a unique opportunity to compare vehicle modeling results with both active and passive radiation measurements. The environment de?nitions and modeling e?orts are described, and a comparison of passive and active measurements is presented with respect to the modeling results.
Citation: Stoffle N, Gaza R, Nounu H, Lee K, and Bahadori A 2016 Comparison of Passive and Active Exploration Flight Test 1 Radiation Detector Measurements with Trapped Proton and Vehicle Shielding Model Calculations NASA/TP-2016-218599 NASA Johnson Space Center: Houston, TX http://ston.jsc.nasa.gov/collections/TRS/415.refer.html
Keywords: BIRD; EFT1; Timepix; Trapped Radiation; Protons; MPCV